(untitled) (Archives of Mechanics - Test, 2001)
The deterioration of the mechanical properties of particulate Metal Matrix Composites (MMCs) caused by macroscopic cracks is studied, experimentally, in comparison to the behaviour of the respective matrix alloys. Two Al-based MMCs, reinforced with fine SiC particles, extensively used in aerospace engineering, are employed. The study is focused on the influence of cracks on the fracture strength of MMCs and on the variation of the critical Crack Opening Displacement (COD) versus the inclination of the crack with respect to the loading direction. The role of the plastic anisotropy induced during manufacturing is also investigated.